2014
DOI: 10.3747/pdi.2013.00056
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Body Mass Index on Outcomes of Peritoneal Dialysis Patients in India

Abstract: ♦ Objectives: We studied the effect of body mass index (BMI) at peritoneal dialysis (PD) initiation on patient and technique survival and on peritonitis during follow-up. ♦ Methods: We followed 328 incident patients on PD (176 with diabetes; 242 men; mean age: 52.6 ± 12.6 years; mean BMI: 21.9 ± 3.8 kg/m 2 ) for 20.0 ± 14.3 months. Patients were categorized into four BMI groups: obese, ≥25 kg/m 2 ; overweight, 23 -24.9 kg/m 2 ; normal, 18.5 -22.9 kg/m 2 (reference category); and underweight, <18.5 kg/m 2 . The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 38 publications
1
41
2
2
Order By: Relevance
“…Contrary to their results, Prasad et al [14] found no changes in HR for mortality between incident patients with BMI >25 kg/m 2 compared to BMI 18.5-22.9 kg/m 2 and 23-24.9 kg/m 2 , with the group of patients with BMI <18 kg/m 2 having an increased HR for mortality. Furthermore, Mehrotra et al [15] performed a study comparing outcomes of continuous ambulatory versus automated PD.…”
Section: Peritoneal Dialysis In Extremely Morbid Obese Patientscontrasting
confidence: 39%
“…Contrary to their results, Prasad et al [14] found no changes in HR for mortality between incident patients with BMI >25 kg/m 2 compared to BMI 18.5-22.9 kg/m 2 and 23-24.9 kg/m 2 , with the group of patients with BMI <18 kg/m 2 having an increased HR for mortality. Furthermore, Mehrotra et al [15] performed a study comparing outcomes of continuous ambulatory versus automated PD.…”
Section: Peritoneal Dialysis In Extremely Morbid Obese Patientscontrasting
confidence: 39%
“…The reported median patient survival in underweight, normal, overweight and obese patients was 26, 50, 57.7 and 49 patient-months, respectively. It was found that obese PD patients had a significantly greater risk of peritonitis [38]. Therefore all the above studies consistently showed that underweight in PD patients conferred worse survival, and this is particularly a problem in Asia where a significant proportion of patients suffer from malnutrition.…”
Section: Issues Related To Peritoneal Dialysis In Asian Countriesmentioning
confidence: 98%
“…Often referred to as the “obesity paradox”, studies in HD patients have consistently demonstrated that higher BMI (BMI >30 kg/m 2 ) is associated with improved survival . In contrast, results have been variable in regards to the association of obesity with mortality in PD patients . In a study directly comparing both treatments in 134 728 incident dialysis patients, the relative mortality risk of PD compared to HD increased with increasing BMI an effect that was more pronounced among diabetic patients .…”
Section: Survival By Modality: Specific Patient Subgroups and Interacmentioning
confidence: 99%
“…[40][41][42][43][44] In contrast, results have been variable in regards to the association of obesity with mortality in PD patients. [45][46][47][48][49][50][51] In a study directly comparing both treatments in 134 728 incident dialysis patients, the relative mortality risk of PD compared to HD increased with increasing BMI an effect that was more pronounced among diabetic patients. 45 However, being underweight, variously defined as <18.5 to <20.9 kg/m 2 , is associated with similarly worse outcomes in both modalities.…”
Section: A Modern Day Perspectivementioning
confidence: 99%